R5 HIV productively infects Langerhans cells, and infection levels are regulated by compound CCR5 polymorphisms - Kawamura, Tatsuyoshi (National Academy of Sciences, 2003)
Langerhans cells (LCs) are suspected to be initial targets for HIV after sexual exposure (by becoming infected or by capturing virus). Here, productive R5 HIV infection of LC ex vivo and LC-mediated transmission of virus to CD4(+) T cells were both found to depend on CCR5. By contrast, infection of monocyte-derived dendritic cells and transfer of infection from monocyte-derived dendritic cells to CD4(+) T cells were mediated by CCR5-dependent as well as DC-specific ICAM-3-grabbing nonintegrin-dependent pathways. Furthermore, in 62 healthy individuals, R5 HIV infection levels in LCs ex vivo were associated with CCR5 genotype. Specifically, genotyping for ORFΔ32 revealed that LCs isolated from ORFΔ32/wt individuals were significantly less susceptible to HIV when compared with LCs isolated from ORFwt/wt individuals (P = 0.016). Strikingly, further genetic analyses of the A-2459G CCR5 promoter polymorphism in ORFΔ32/wt heterozygous individuals revealed that LCs isolated from -2459A/G + ORFΔ32/wt individuals were markedly less susceptible to HIV than were LCs from -2459A/A + ORFΔ32/wt individuals (P = 0.012). Interestingly, these genetic susceptibility data in LCs parallel those of genetic susceptibility studies performed in cohorts of HIV-infected individuals. Thus, we suggest that CCR5-mediated infection of LCs, and not capture of virus by LCs, provides a biologic basis for understanding certain aspects of host genetic susceptibility to initial HIV infection.